GROUNDWATER FLOW OF THE AKHURYAN RIVER BASIN: (in the territory of the Republic of Armenia) (Proceedings of the YSU C: Geological and Geographical Sciences, 2016)
In the article, based on the materials of deciphering aerial photographs, geophysical studies and water balance calculations for the Akhuryan River basin has been compiled a relief map of the regional impermeable rocks. A centered way of groundwater movement (paleovalleys) has been installed and estimated the value of the groundwater flow of the basin. The obtained data can be used for more detailed and targeted prospecting and exploration of water.
Keywords: precipitation; infiltration; aquitard; groundwater runoff; paleorelief; watershed; geophysical surveys; basin; a module flow path